2016
DOI: 10.1038/jp.2015.199
|View full text |Cite
|
Sign up to set email alerts
|

Breastmilk from obese mothers has pro-inflammatory properties and decreased neuroprotective factors

Abstract: OBJECTIVE To determine the impact of maternal obesity on breastmilk composition. STUDY DESIGN Breastmilk and food records from 21 lean and 21 obese women who delivered full-term infants were analyzed at 2 months post-partum. Infant growth and adiposity were measured at birth and 2 months of age. RESULT Breastmilk from obese mothers had higher omega-6 to omega-3 fatty acid ratio and lower concentrations of docosahexaenoic acid, eicosapentaenoic acid, docasapentaenoic acid and lutein compared with lean mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 45 publications
2
100
0
3
Order By: Relevance
“…Lipid factor 2 was composed of saturated fatty acids including palmitic acid, which alone was higher in OW/OB mothers. The higher palmitic acid may reflect an overall higher concentration of saturated fatty acids related to dietary intake in mothers with increased weight status and leads to mixed infant outcomes (Jenkins, West, & Koulman, ; Panagos et al, ; Petersen et al, ; Pfeuffer & Jaudszus, ; Vidakovic et al, ). This is consistent with a lack of relationship of lipid factor 2 with infant weight and length growth in our cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid factor 2 was composed of saturated fatty acids including palmitic acid, which alone was higher in OW/OB mothers. The higher palmitic acid may reflect an overall higher concentration of saturated fatty acids related to dietary intake in mothers with increased weight status and leads to mixed infant outcomes (Jenkins, West, & Koulman, ; Panagos et al, ; Petersen et al, ; Pfeuffer & Jaudszus, ; Vidakovic et al, ). This is consistent with a lack of relationship of lipid factor 2 with infant weight and length growth in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a positive association between milk N6:N3 LC‐PUFA ratio and infant growth from 2 weeks to 6 months with higher infant WFA, WFL, and BMI Z ‐score change in infants receiving any degree of human milk with continued positive trends in EHM‐fed infants. Panagos et al () showed that increased N6:N3 LC‐PUFA ratio was associated with increased WFL Z ‐score at 2 months. On the other hand, a human supplementation study showed that milk N6 LC‐PUFAs were negatively associated with infant BMI and lean body mass at 4 months and increased N3 LC‐PUFAs in milk stimulated early fat accumulation (Much et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…7 A few studies have suggested that human milk of obese women has a different fatty acid pattern compared with that of normal weight mothers while total fat content may be similar in both groups. 8,9 To the best of our knowledge, the colostrum of obese women was analyzed in only one study and was shown to be higher in fat and caloric content than in non-obese women. 10 Conversely, it is unclear whether the milk of underweight mothers is adequate in terms of macronutrient content.…”
Section: Introductionmentioning
confidence: 97%
“…However, whether breastmilk from obese mothers is as efficacious for infant immunity as milk from their nonobese counterparts has been yet to be studied. A study done comparing lean and obese mothers demonstrated that breastmilk from obese mothers had an increase in proinflammatory factors, a higher omega 6 to omega 3 ratio, and a decrease in neuroprotective agents (41). By studying the physiological changes at the level of the mammary gland, we can further understand how obesity affects mammary gland physiology during lactation.…”
Section: Introductionmentioning
confidence: 99%